Tactical level operating theatre scheduling of elective surgeries for maximizing hospital performance. (December 2022) - Yang, Xiankai; Gajpal, Yuvraj; Roy, Vivek; Appadoo, Srimantoorao
Highlights: Operating theatre scheduling problem with both upstream and downstream resources limitation. The objective is to minimize total net revenue. Variable neighborhood search is used to solve the problem. Proposed method can solve problem with different hospital sizes in reasonable CPU time. Sensitivity analysis is performed to understand the ways to improve the hospital performance. Abstract: Tactically, surgical operations are an important frontier of health care systems that involves treatment of injuries, diseases, and other disorders by manual and instrumental means. Further, this frontier constitutes a significant portion of budget in health care systems to provide quality services. Efficient management of operating theatre can reduce costs and increase patients' satisfaction to enhance hospital performance. Elective surgery within this segment can be scheduled in advance, and can thus yield significant efficiency through efficient management and planning. This paper considers an elective surgery scheduling problem at the tactical level. The problem mainly determines the number of sessions for each department, and the number of treated patients for each surgery type. The problem considers multiple objectives, including maximizing the hospital performance and revenue, and minimizing the number of overdue patients, number of patients on the waiting list, and weighted overdue patients. Variable neighborhood search (VNS) algorithm is used in this research to solve the operating scheduling problem. A numerical experiment is performed in the randomly generated data set to evaluate the effectiveness of the proposed algorithm. Sensitivity analysis is performed to understand the ways to improve the hospital performance. By using the VNS algorithm in elective surgery operating room scheduling, we hope to increase patients' satisfaction and reduce the cost of hospitals at the same time.